2021
DOI: 10.1002/emp2.12400
|View full text |Cite
|
Sign up to set email alerts
|

Trends and variation in repeat neuroimaging for children with traumatic intracranial hemorrhage

Abstract: Objectives We aimed to determine trends and institutional variation in repeat neuroimaging in children with traumatic intracranial hemorrhage and to identify factors associated with neuroimaging modality (subsequent magnetic resonance imaging [MRI] vs computed tomography [CT]). Methods We conducted a retrospective cross‐sectional study of 35 hospitals in the Pediatric Health Information System database. We included children <18 years of age hospitalized from 2010–2019 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Children with tICH are often admitted for close clinical monitoring and repeat neuroimaging to screen for hemorrhage progression resulting in clinical deterioration. The specifics of management, including monitoring location (inpatient floor vs ICU), duration of monitoring, and use, timing, and modality of repeat neuroimaging (CT vs MRI), varies significantly by institution 12,15 . In our sample, we identified measurable rates of interventions and deterioration after injury and found that care was driven by a combination of factors including clinical course and neuroradiographic findings.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Children with tICH are often admitted for close clinical monitoring and repeat neuroimaging to screen for hemorrhage progression resulting in clinical deterioration. The specifics of management, including monitoring location (inpatient floor vs ICU), duration of monitoring, and use, timing, and modality of repeat neuroimaging (CT vs MRI), varies significantly by institution 12,15 . In our sample, we identified measurable rates of interventions and deterioration after injury and found that care was driven by a combination of factors including clinical course and neuroradiographic findings.…”
Section: Discussionmentioning
confidence: 92%
“…The specifics of management, including monitoring location (inpatient floor vs ICU), duration of monitoring, and use, timing, and modality of repeat neuroimaging (CT vs MRI), varies significantly by institution. 12,15 In our sample, we identified measurable rates of interventions and deterioration after injury and found that care was driven by a combination of factors including clinical course and neuroradiographic findings. The variability in management not only highlights the need for improved risk stratification, but also the need for a more granular understanding of clinical course to guide management decisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations